3D-CINEMA AND HEADACHE: THE FIRST EVIDENTIAL RELATION AND ANALYSIS OF INVOLVED FACTORS - Mark eBraschinsky; Mark eBraschinsky; Liis eSabre; Liis eSabre; Aire eRaidvee; Nadzeja eZmachinskaja; Olga eZukovskaja; Anti eKarask; Bruno eSaar; Aleksei eRakitin (Frontiers in Neurology, 2016)
Background. A possible link between 3D-movies and headache (HA) has never been a target of specific and systematic investigations. The aim of this study was to investigate the relationship between 3D-cinema and HA and to evaluate possible risk factors of developing HA during or after watching a 3D-movie.Methods. This was a prospective, non-randomised, observational study. Six thousand specifically designed questionnaires were distributed to consecutive cinema visitors. Relative HA risks for 2D- vs 3D-movie visitors, and the effects of background variables were analysed.Results. The questionnaire was filled and returned by 1293 persons. The mean age of responders was 33.0 ± 11.3 years. Individuals who viewed 3D-movies reported HA during or after the movie 1.61 times more often than 2D-movie viewers (11.1% in 3D vs 7.2% in 2D-movies, p=0.017). The risk was higher in women: 2.65 times for 2D (p=0.019) and 1.85 times for 3D-movies (p=0.06), and decreased with age by 4.6% with each year for 2D (p=0.0035) and by 3.2% for 3D-movies (p=0.0098). Among 3D-movie visitors, those with previous HAs were 4.17 times more prone to get a cinema-induced HA (p=0.02). The risk was the highest for persons with migraine (OR=3.37, p=0.001). Conclusions. For the first time it was evidentially shown that 3D-movies can provoke HA. Persons at risk are mostly younger women and/or migraineurs. Based on our results, for those belonging to the aforementioned risk groups it can be mainly recommended to choose passive 3D technology and to view movies from the farthest possible distance.